Hella town : Oakland's history of development and disruption - Schwarzer, Mitchell (University of California Press, 2021)
"Oakland is a well-kept secret, a port city of dramatic topography and physical beauty, varied social groups and one-off neighborhoods. In his incisive history, Mitchell Schwarzer examines the development of Oakland's built environment from the onset of the twentieth century to the present, especially in light of its status as a second city playing underdog to glamorous San Francisco across the bay. His book emphasizes the ways transportation networks, housing, industry, commerce, and civic and park projects together shaped a social and political terrain that continues to be defined by class and racial inequalities"--